Gain Enhancement of a Microstrip Patch Antenna Using I-Shaped Defective Ground Structure - Dr. CN. Sujatha, Ms. Nausheen Sultana, D. Anusha, B. Sushmitha, G. Sravani (International Journal of Advanced Science and Technology, 2020)
The technology in an Antenna evolved with increase in designing of various antennas that could be used to work for various applications. Now-a-days huge frequency producing signals are preferred for any type of communication. Microstrip patch antennas which are also called as MPA could be one of the examples which would satisfy the need of this huge frequency producers. The attributes involved in the design of this antenna are in the enhanced format. In this paper, conventional microstrip antenna is given enhancement of gain by providing defected ground structure. The substrate used here is of relative permittivity or dielectric constant of 2.2. Ansys HFSS software is employed to design the antenna as it puts forth all the results that an antenna would radiate to give. A clear-cut view of antenna’s radiating frequency is shown by this software. Co-axial feeding technique is incorporated to input or feed the antenna. Gain development has been the prime motto to design the antenna. This gain enhancement is achieved by introducing defective ground structure. It gives a gain of 10dB and radiates at a frequency of -20.92 at 7.88GHz.  The above statement gives us an idea that the antenna would radiate in the X band which ranges from 4GHz to 8GHz.